2018
DOI: 10.1021/acsami.8b16120
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Highly Porous Polymer Membranes with Hierarchical Porous Structures via Spinodal Decomposition of Mixed Solvents with UCST Phase Behavior

Abstract: The predominant method to prepare polymer membranes is based on phase inversion. However, this method always leads to a dense skin with low porosity when normal polymers are used. Using the self-assembly of certain block copolymers, it is possible to prepare uniform pores with high porosity, but the prices of these polymers are too high to be afforded in practical applications. Here, we report a novel strategy to prepare highly porous and asymmetric polymer membranes using the widely used poly(vinylidene fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…The detail membrane preparation procedure and the pore-forming mechanism can be found in previous work. 27 The Fourier transform infrared spectra (FTIR) in Figure 1c revealed that the PVDF membrane contained α, β, and γ three types of crystalline phases. Figure 1d shows the uptake curve of the PVDF membrane versus time with the electrolyte of 1 M LiTFSI in DOL/DME.…”
Section: Resultsmentioning
confidence: 99%
“…The detail membrane preparation procedure and the pore-forming mechanism can be found in previous work. 27 The Fourier transform infrared spectra (FTIR) in Figure 1c revealed that the PVDF membrane contained α, β, and γ three types of crystalline phases. Figure 1d shows the uptake curve of the PVDF membrane versus time with the electrolyte of 1 M LiTFSI in DOL/DME.…”
Section: Resultsmentioning
confidence: 99%
“…1 depicts the significance of porous polymers, as an increasing trend in the number of publications devoted to porous polymers is observed in the last decade. Ease of melt or solution processing of polymers in various shapes and sizes and feasibility for chemical modifications have made them a material of interest for developing different porous architectures in the form of electrospun fibres, 4 membranes, 5 beads, 6 monoliths, 7 etc. Porous polymers adorned with several fascinating properties like low specific density, high specific strength, high surface area and controlled porosity with tunable pore-size have thus been used in numerous household and industrial applications as adsorbents, 8 membranes for water purification, 9 gas storage, 10 catalysis, 11 sensors, 12 precursor materials for porous carbons, 13 packaging materials in chromatography columns, 14 encapsulating agents for controlled drug release 15 and scaffolds for tissue engineering, 16 to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Porous materials have attracted wide attention because of their useful functionalities and microstructures for various applications in including catalytic supports, thermal insulators, sound absorbers, adsorbents, energy materials, and separation membranes [1][2][3][4][5][6]. For several decades, the synthesis routes of porous materials have typically involved chemical approaches, such as the hydrothermal method, sol-gel method, and gasphase synthesis like the spray pyrolysis method [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%